Estudo microscópico comparativo entre as Osteonecroses e as Osteomielites dos maxilares - De Antoni, Carlos Cesar (2016)
The osteomyelitis and osteonecrosis are important bone disorders that the jaws. They may have similar clinical and radiographic features, being challenger to the pathologist to report the final nosologic diagnosis only with the microscopic analysis. Faced with few studies addressing the microscopic aspects of these entities, the aim of this study was to evaluate if there is microscopic difference between osteomyelitis (OM), drug osteonecrosis associated with bisphosphonate (MRONJ) and osteoradionecrosis (ORN); present the differences between them when it had and consider if it is possible to report the diseases only with microscopic examination. The study was retrospective, with specimens previously undergone biopsy of the maxillary bones, affected by the three diseases. 6 specimens of OM were obtained, coming from USC; 16 of MRONJ, coming from the Hospital Santa Catarina and 22 ORN, coming from the Erasto Gaertner Hospital in Curitiba, totaling 44 samples. Two pathologists examined the specimens, without the knowledge of the diagnosis. Microscopic aspects evaluated were: bone material, inflammatory infiltrate, blood vessels and the presence of microorganisms, which were recorded in a standard table for both examiners. Furthermore, the examiners have issued a hypothesis diagnosis of each specimen. Considering the evaluated structures, there was total agreement among examiners (Kappa = 1). They were statistically significant only the presence of empty channels, which was less frequent in the ORN (p = 0.042) and the presence of neutrophils, which was well below the MRONJ group (p≤0,001). There was no consistent diagnostic suggestion of this disease among examiners (Kappa = 0.23). From the analysis of this study, it was concluded that the disease compared (OM, ORN and MRONJ) had a lot of microscopic resemblance, especially with regard to the presence of necrotic bone, inflammation and microorganisms. Moreover, it is not possible to obtain the diagnosis of diseases assessed only with the microscopic analysis. Clinical information is fundamental to the establishment of the final diagnosis